PENGARUH PENDIDIKAN GIZI DENGAN MENGGUNAKAN MEDIA KOMIK TERHADAP PENGETAHUAN GIZI SEIMBANG ANAK KELAS 5 SEKOLAH DASAR DI SDN CIRIUNG 02 CIBINONG TAHUN 2017 - Sintha F S; Nadya Anggraeni (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2018)
Guidelines for balanced nutrition began to be introduced and socialized more than 15 years ago. Guidelines for balanced nutrition apply to every stage of age including school-aged children. Education of balanced nutrition is still little given to school-aged children. According to some research is still a lot of prevalence of knowledge of balanced nutrition is lacking. In the study conducted Zulaekah (2012) showed that as many as 57.7% of primary school children have a lack of nutrition knowledge. This study aims to determine whether there is influence of nutrition education by using Comic media on knowledge of balanced nutrition. In this research use quasy experimental research design with time series design design. This research is done by using comic print media which contains about 4 messages of balanced nutrition, that is variation of food, the importance of clean life, the importance of active lifestyle and exercise, and the importance of monitoring the weight which is visualized in a tumpeng gizi seimbang (TGS). Statistical analysis of data using t-dependent test. The result of t-dependent test shows that there is an increase of average value of knowledge before and after giving comic 36,36. In this research, balanced comic nutrition media can increase the average knowledge of schoolchild by 34,36 or 72,15%.